A secure image encryption method using scan pattern and random key stream derived from laser chaos. (April 2019) - Sivakumar, T.; Li, Pu
Highlights: Our method uses random keys from optical chaos to achieve the image encryption. Our method only needs single iteration, but can achieve a significant performance. Our method resists the security attacks and takes less time for encryption. Abstract: Internet allows people in any corner of the world to share instantly all types of information. Secure sharing of sensitive multimedia data necessitates confidentiality service, which is offered by encipherment mechanism. In this paper, a fast and secure image encryption method using scan patterns and true random key streams is proposed. The scan pattern is used to scramble the original image by means of pixel permutation. The random key stream is generated employing a photonics based approach and then used to perform a bitwise XOR operation to get the encrypted image. The proposed method takes very less time for encryption and has substantial resistance with statistical, differential and entropy attacks.